Non-contrast computed tomography in acute ischaemic stroke: a pictorial review - Hassan, Radhiana; Sharis Osman, Syazarina; Mohamed Mukari, Shahizon Azura; Hashim , Hilwati; Muda, Ahmad Sobri (Malaysian Medical Associations, 2013)
Non-contrast computed tomography (NCCT) remains a widely used imaging technique and plays an important role in the evaluation of patients with acute ischaemic stroke. However,the task ofidentifying the signs of acute ischaemia and quantifying areas of brain involvement on NCCT scan is not easy due to its subtle findings. The reliability of arly ischemic sign detection can be improved with experience, clinical history and the use of stroke window width and level on viewing the images. The Alberta Stroke Program Early CT Score (ASPECTS) was developed to overcome the difficulty of volume estimation in patients eligible for thrombolysis. It is a systematic, robust and practical method that can standardized the detection and reporting of the extent of acute ischaemic stroke. This article serves as an educational material that illustrates those findings which are important for all clinicians involved in acute stroke care